Diagnostic accuracy of an in-house ELISA using the intermediate species Leptospira fainei as antigen for diagnosis of acute leptospirosis in dogs. (February 2017) - Penna, Bruno; Marassi, Carla D.; Libonati, Hugo; Narduche, Lorena; Lilenbaum, Walter; Bourhy, Pascale
Highlights: The purpose was to determine the usefulness of a L. fainei -based ELISA for the diagnosis of acute canine leptospirosis. ELISA-Hb was easily performed and with little variation, what confirms its repeatability. ELISA-Hb was highly sensitive (95.6%) and specific (93%) in differentiating acutely infected dogs from chronically infected ones. The results of the ELISA-Hb protocol for the diagnosis of the clinical acutely infected canines with leptospirosis were very encouraging. Abstract: Diagnosis of animal leptospirosis is still challenging. The microscopic agglutination test, is the current method for diagnosing leptospirosis. However, this technique requires specific equipment, highly trained staff and the maintenance of live cultures of several reference strains of Leptospira for use as antigens. Recently, an ELISA (enzyme-linked immunosorbent assay) employing a Leptospira fainei serovar Hurstbridge based antigen for the early diagnostic of human leptospirosis was developed. In this study we estimate the diagnostic sensitivity and specificity of this test in identifying acute canine leptospirosis. A total of 271 serum samples divided into five panels and tested by MAT as a reference test, were used to evaluate the ELISA. Comparing acutely and non-acutely infected dogs, ELISA-Hb showed 95.6% sensitivity and 93% specificity. L. fainei -based ELISA is adequate for diagnosing acute canine leptospirosis, with high sensitivity and specificity and presenting practical advantages when compared to current techniques.